Efficacy Assessment of Lemon Peel Aromatherpy Againts Airborne Bacteria Experimental Study in ICU Room of Sultan Agung Islamic Hospital Semarang - Sari, Merin Awu; Masfiyah, Masfiyah; Chodidjah, Chodidjah (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Background: Healthcare associated infections (HAI) are infections acquired in health care centers such as hospital, clinic or other health care sites due to microorganisms. Research conducted by WHO showed 3-10% of all patients treated in hospitals were victims of HAI and 90% were mainly caused by bacteria, the rest by viruses, fungi or protozoa. Lemon peel aromatherapy is one of the essential oils from plants having antimicrobial activity and are beneficial to health reducing bacterial growth by inhibiting the function of cell membranes. This study aimed at evaluating the efficacy of lemon peel aromatheraphy againts airborne bacteria.Design and Method: This experimental study used post test only control groups design. The number of airborne bacteria colonies obtained from ICU room of Sultan Agung Islamic Hospital Semarang treated with lemon peel aromatherapy at the concentration of 100 % and the control group (-).The data were analyzed for normality using Shapiro Wilk followed by independent T-test Result: independent inT-test Independent showed a significant differences in the number of bacterial colonies between the treated groups receiving 100% concentration of lemon peel aromatherapy and control group (-) (p < 0.045).Conclusion: Aromatherapy extracts of lemon peel has effect on reducing the number of airborne bacteria in the ICU of Sultan Agung Islamic Hospital Semarang (Sains Medika, 4(1):71-77).